(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The researcher used the experimental curriculum to suit the nature of the research. The research sample was formed from the 26 students, and the program took 16 learning units by two units per week. The researcher concluded that the educational program has a positive effect in developing the flexibility of thinking and learning the skill of evasiveness in students and recommended the researcher the following: 1. development of creative thinking for all stages of preparatory because of its role in the process of learning motor skills. 2. Develop educational programs that mimic mental habits when teaching basic skills in football.